Theoretical study of the dilemma in the consumption of green products - Wangsa, Ignasius Heri Satrya (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2023)
Participation in implementing green behavior is often a dilemma and an exciting study for many researchers. Through this research, a theoretical study of dilemmas in the consumption of green products is conducted by searching for international journal articles. In this study, a five-stage method of data processing of research journal articles was applied, including (1) Stage-1: Article search using Dimensions software; (2) Stage-2: Selection of one main article; (3) Stage-3: Searching articles related to prior works using Connected Papers software; (4) Stage-4: Processing articles based on the work cloud using ATLAS. ti software; and (5) Stage-5: Searching and processing articles using VOSviewer and Biblioshiny software. The articles collected were 637 articles (Stage-1) and 1946 (Stage-5). The conclusions obtained through this study are: (1) Studies on dilemmas in green product consumption need to be followed up through comprehensive follow-up studies; (2) Potential areas of study include: (a) the level of belief in green products that explains the rationalization of green product consumption; (b) economic and social aspects that critique the advantages and disadvantages of green product consumption.